EFFECT OF MOISTURE WOOD-FIBER BOARD ON THE PROCESS OF BENDING - Pylypiv, Igor (Forestry, Forest, Paper and Woodworking Industry, 2012)
Analyzed the results of studies the impact moisture on the radius of bending plates different thickness after applying PVA glue on one and two sides with different exposure time. Found that for all thicknesses of both unilateral and bilateral moistening occurs optimal exposure time after applying the adhesive to the bending process. The study allowed us to obtain the minimum values of radius for each thickness of plates at one and two sided moisture.